حماية المستهلك من جريمة الغش في المنتوجات في التشريع الجزائري (El-Wahat Journal for Research and Studies, 2020)
The Issue Of Consumer Protection Is One Of The Thorny And Complex Issues That Give Rise To Problems. As For The Increased Risks Of Fake And Non-Conforming Products, The Legislator Needed To Intervene To Criminalize Certain Behaviors, And To Protect The Consumer.The Algerian Legislator Provided For Penalties For Each Perpetrator Of The Crime Of Fraud In Order To Suppress And Deter Violators, Ramat, As Well As Supplementary And Other Administrative Sanctions. Key Words-Consumer, Economic Aid, Product Fraud, Penalty.